Themes, Rhetoric, and Conceptual Metaphors in the Titles of Persian Ornamental Prose Texts - Abdullah Albughobaish; Asghar Esmaeili (تاریخ ادبیات, 2024)
The titles of literary texts from each historical period provide substantial and valuable data about their authors and the social and cultural developments of the society of that period, among other matters. Given their artistic and literary nature, the titles of Persian ornamental prose texts can reveal cultural and literary approaches in different periods of Iranian literary history, in addition to historical or social facts. Based on this idea and by adopting the historical reference method in collecting data, this study attempts to analyze the titles of 38 ornamental prose texts in the history of Persian literature based on their rhetoric, themes, and conceptual metaphors. From an aesthetic viewpoint, the current study identifies two subgroups of the titles, literary and non-literary. It also places two subgroups under the larger literary group: rhymed titles and metaphorical ones. Moreover, the more the content of a work tends towards the objective, the more the title becomes rhymed. On the other hand, the more the content tends towards the abstract, the more the title becomes metaphorical. Also, the non-literary and functional titles are almost devoid of the aesthetic aspect. According to this study, the broadest range of titles belongs to historical topics, which we can notice in all types and sub-genres of titles. This wide range is a product of the intellectual system that governed the political classes and indicates the dual relationship between the ruler and the educated on the one hand and a kind of estrangement between the political classes and the masses of society at that time in Iran on the other hand. Regarding the purpose of choosing the title, some titles have a motivational nature, some have a functional nature, and some have a complex mixed nature. In another part of the research, using the idea of conceptual metaphors, it is shown that the semantic fields of direction and movement, as well as plants, are the most used; the reasons for these are explained in the research.